Modeling the equatorial and low‐latitude ionospheric response to an intense X‐class solar flare - Nogueira, P. A. B. (2015)
We have investigated the ionospheric response close to the subsolar point in South America due to the strong solar flare (X2.8) that occurred on 13 May 2013. The present work discusses the sudden disturbances in the D region in the form of high‐frequency radio wave blackout recorded in ionograms, the E region disturbances in the form of the Sq current and equatorial electrojet intensifications, and the enhancement and decay in the ionospheric total electron content (TEC) as observed by a network of Global Navigation Satellite Systems receivers, the last of these manifestations constituting the main focuses of this study. The dayside ionosphere showed an abrupt increase of the TEC, with the region of the TEC increase being displaced away from the subsolar point toward the equatorial ionization anomaly (EIA) crest region. The decay in the ΔTEC following the decrease of the flare EUV flux varied at a slower ratio near the EIA crest than at the subsolar point. We used the Sheffield University Plasmasphere‐Ionosphere Model to simulate the TEC enhancement and the related variations as arising from the flare‐enhanced solar EUV flux and soft X‐rays. The simulations are compared with the observational data to validate our results, and it is found that a good part of the observed TEC variation features can be accounted for by the model simulation. The combined results from model and observational data can contribute significantly to advance our knowledge about ionospheric photochemistry and dynamics needed to improve our predictive capability on the low‐latitude ionospheric response to solar flares.